Desentralisasi fiskal dan pengaruhnya terhadap kinerja penyerapan belanja daerah di Indonesia - Tomi Setiawan; Muhammad Farras Samith; Muhammad Hammam Mughits; Shifwah Murran Nashifa (Nur Science Institute, 2026)
This study examines the effect of fiscal decentralization on regional budget absorption performance in Indonesia, using panel data from 34 provinces for 2021–2023. The analysis method employed is fractional probit regression with the Mundlak approach, along with a robustness test using Quasi Maximum Likelihood Estimation (QMLE). The results indicate that fiscal decentralization, both in revenue and expenditure, has a positive, statistically significant impact on the probability of regional budget absorption. Regions with higher fiscal autonomy and higher expenditure-to-revenue ratios tend to exhibit better budget absorption performance. In addition, fiscal independence also contributes positively to expenditure absorption. Simultaneously, several control variables, such as population growth, show a positive effect, while others, including the unemployment rate, GRDP per capita, and population density, have a significant negative impact. These findings emphasize the importance of strengthening local fiscal capacity and regional institutional quality to improve budget management effectiveness and ensure the successful implementation of fiscal decentralization.